Analysis of the difficulty index of item bank according to cognitive aspects during the Covid-19 pandemic - Maizura Fauzie; Andi Ulfa Tenri Pada; Supriatno Supriatno (Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
The Covid-19 pandemic is a major challenge for the education system. The face-to-face learning process shifted to online learning, including the school exams. In Aceh province, the school exams have changed from paper-based and computer-based. This research aims to analyze the difficulty index of an item bank based on cognitive aspects of Bloom’s Taxonomy. The study samples included 850 students. The data were the item bank of a final semester exam consisting of 200 multiple-choice items, answer keys, and students’ answer sheets. The empirical analysis of the item bank using classical test theory (CTT) found that 141 out of 200 items are valid based on content validity and computing data set using the Aiken’s V formula. Item tests have reliability of 0.983. The reliability is calculated using the Kuder-Richardson 21 formula. If the reliability coefficient is r11 ≥ 0.70, then the item is declared reliable. In addition, 62 out of 141 (43.97%) items from the item bank are classified with a moderate difficulty index, and 79 items (56.03%) are categorized with a high difficulty index. The cognitive aspects found in the items are remembering, understanding, applying, and analyzing. Students mostly found items with the cognitive aspects of remembering and understanding are difficult to solve.